Vanadium Induces Oxidative Stress and Mitochondrial Quality Control Disorder in the Heart of Ducks - Xiong, Zhiwei; Xing, Chenghong; Xu, Tianfang; Yang, Yan; Liu, Guohui; Hu, Guoliang; Cao, Huabin; Zhang, Caiying; Guo, Xiaoquan; Yang, Fan (Frontiers in Veterinary Science, 2021)
Vanadium (V) is an ultra-trace element presenting in practically all plants and animals. The mitochondrion is an essential organelle for maintaining cell functions. Excessive V can cause oxidative stress and mitochondrial dysfunction and subsequently influence cells or organs' functions, but the relationship between excessive V and mitochondrial quality control (MQC) is unclear. To investigate the effect of excessive V on oxidative stress and MQC in duck hearts, seventy-two ducks were randomly divided into two groups, including the control group and the V group (30 mg of V/ kg dry matter). The cardiac tissue was collected at 22 d and 44 d to observe the morphologic changes, assess the contents of H2O2 and MDA and the activities of T-SOD and CAT, detect mitochondrial biogenesis, mitochondrial fission and fusion and mitophagy related mRNA and protein levels. Results showed that excessive V could trigger vacuolar degeneration, granular degeneration of myocardial cells, and mitochondrial vacuolization, swelling and crest disappeared. Additionally, excessive V could cause CAT activity to increase in two-time points, but T-SOD activity was increased in 22 d and decreased in 44 d. Meanwhile, excessive V intake could increase the number of Drp1 puncta, and the mitochondrial fission (Drp1and MFF) related mRNA and protein levels, but decrease both the number of Parkin puncta and the mitochondrial biogenesis (PGC-1α, NRF-1, and TFAM), mitochondrial fusion (OPA1, Mfn1, and Mfn2), and mitophagy (Parkin, PINK1, P62, and LC3B) mRNA and protein expression levels. Collectively, our results suggested that excessive V could induce MQC disorder and oxidative stress in the heart of ducks.